Socioeconomic level as an error generating variable in racial studies - Passos, A. D.; Cardoso, J. C.; Paz, J. E.; Castilla, E. E. (Revista de Saúde Pública, 1978)
The influence of the socio-economic level on biologic variables such as birth-weight, gestational age and birth order was studied in 734 single live-born deliveries at five Brazilian maternities. Live-borns were classified into ethnic groups according to the races of their ancestors. Socio-economic level was found to be associated with birthweight and birth order, acting therefore as an error - generating variable in racial studies.